Effect of COVID-19 pandemic on gender based violence: a study on TMSS microcredit members - Sultana, Most Aeysha; Rahman , Arifa (Dhaka University Journal of Biological Sciences, 2024)
The present study was aimed at investigating if the COVID-19 outbreak had an impact on gender-based violence (GBV) among TMSS microcredit users. The study was designed to gather data using both quantitative (individual interviews) and qualitative (Focus Group Discussion) method. One hundred and eighty-five married women of Bogura district made up the sample. The sample included 159 microcredit members and 26 non-members. Majority of the participants experienced financial hardships during the COVID-19 epidemic, according to quantitative and qualitative data. Quantitative data showed that a significant portion of microcredit participants (56%) experienced physical, mental, or both types of violence from their husbands during the lockdown. However, the TMSS Microcredit members had greater exposure to GBV than non-members, according to qualitative findings. The same factors—such as income loss, staying at home constantly, and concern about providing for family needs—were highlighted by both microcredit members and non-members as probable causes for the rise in violence during lockdown. But microcredit members mentioned that the lack of microcredit loans and the pressure to make loan payments also resulted in violence against women during lockdown. Quantitative data also indicated that women who experienced violence from their husbands had trouble accessing medical care and law enforcement support. The present study recommended that during emergency situation the microcredit providers should take different policies to help people cope with their financial crisis and government and non-government organizations should take safeguards to prevent gender based violence. Dhaka Univ. J. Biol. Sci. 33(1): 57-65, 2024 (January)